2011
DOI: 10.1002/ijc.25818
|View full text |Cite
|
Sign up to set email alerts
|

Human tumor microRNA signatures derived from large‐scale oligonucleotide microarray datasets

Abstract: The expression profiles of microRNAs (miRNAs) are associated with the initiation and progression of human tumors. DNA microarrays are widely used to explore the expression patterns of miRNAs. Because of the limited sample size and experimental expense, the statistical power of individual research projects is not sufficient to yield a robust conclusion. However, collected microarray datasets of expression profiles provide opportunities to compile the information of individual studies. Our study carried out a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 48 publications
7
72
0
Order By: Relevance
“…Xin et al (18) reported that miR-154 remarkably suppressed cell proliferation, colony formation, migration and invasion in colorectal cancer cells by targeting Toll-like receptor 2. Wang et al (32) reported that overexpression of miR-154 suppressed tumor cell malignance and G1/S transition in hepatocellular cancer cells by targeting CCND2. In the present study, miR-154 could significantly inhibit the migration and invasion of NSCLC cells by targeting ZEB2.…”
Section: Discussionmentioning
confidence: 99%
“…Xin et al (18) reported that miR-154 remarkably suppressed cell proliferation, colony formation, migration and invasion in colorectal cancer cells by targeting Toll-like receptor 2. Wang et al (32) reported that overexpression of miR-154 suppressed tumor cell malignance and G1/S transition in hepatocellular cancer cells by targeting CCND2. In the present study, miR-154 could significantly inhibit the migration and invasion of NSCLC cells by targeting ZEB2.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent experiments confirmed that miR-154 directly targets CCND2 in hepatocellular carcinoma (HCC), reduces tumorigenicity and inhibits the G1/S transition in cancer cells. 38 In line with these findings, our luciferase reporter assay results show that CCND2 is also targeted by c-miR-Ch9 as depicted by the decreased activity of the reporter gene in wild-type binding site conditions and the increased activity in mutated binding site conditions. Moreover, addition of anti-c-miR-Ch9 LNA to pGL4-10 + wt-Triplet conditions reduced regulation as shown by the observed increase in the reporter gene activity.…”
Section: Methodssupporting
confidence: 85%
“…This target site was further confirmed by four other tools (TargetScan, StarMir, 24 PITA, DianaMicroT) which were used to perform target prediction using our novel miRNA sequence. The gene corresponding to this 3'UTR was CCND2, a gene with documented oncogenic activity 38 that is known to play a role in the G1/S transition of the cell cycle.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations